STEADY STATE FINITE ELEMENT ANALYSIS OF A SINGLE STACK COLD PLATE WITH HEAT LOSSES - G. A. Quadir; Shiao Lin Bell; K. N. Seetharamu; A. Y. Hassan (Universitas Gadjah Mada, 2002)
Steady state analysis of a single stack cold plate used for the cooling of electronic components is carried out using the finite element method. The present methodology takes into account the heat losses from the top and bottom surfaces of the stack. In addition dimensionless parameters are used in the analysis. The analysis is divided into two parts: a single unit cell analysis and the analysis of the assembly of several unit cells. The results from the present analysis of a single unit cell for single stack cold plate without heat losses compare well with those available in the literature. The analyses of the assembly of unit cells with heat losses from the top and bottom surface of the stack show that the single unit cell can be considered to be the representative of the stacks only when there are no heat losses.